Efeito agudo da Contração Voluntária Isométrica Máxima (CVIM) com adição de vibração mecânica sobre o desempenho em corrida de velocidade - Roberto de Santis (2016)
Several studies have verified the acute effects of different preconditioning activities on sprint performance. The aim of this study was to investigate the acute effect of Maximum Voluntary Contraction (MVC) with the addition of mechanical vibrations on sprint test performance. The sample consisted of 8 young male sprinters, age 20.23 ± 2.46 years, body weight 69.9 ± 4.2 kg, height 1.77 ± 0.05 and personal best on 100 m 11.14 ± 0, 32 s. Each athlete participated in three separate trials: Maximum Voluntary Contraction (MVC), MVC with the addition of mechanical vibration (MVC + VIB) and control (CON), on non-consecutive days, using randomized treatment sessions (1 treatment per session). In MVC condition, athletes performed a 5s maximal isometric contraction of the lower limbs as preconditioning activity, while on the condition VIB + MIVC performed the same contraction with the addition of mechanical vibration (26 Hz, 6 mm). In all conditions, the dependent variable for comparison the different pre-conditioning activities was the time at 40m sprint test, including the split times at 10, 20, 30 and 40m, recorded immediately after the contraction (0 min) and after 8 minutes of active rest (8 min). Results indicated no significant differences in split times at 10 and 20 m between the conditions. In the 30m split time, a significant difference was found between the MVC 0 min and MVC +VIB 8 min conditions (3.94 ± 0.12 s vs. 3.85 ± 0.13 s). In the 40m split time between MVC 0 min and MVC 8 min conditions (5:01 ± 0:17 vs. 4.91 ± 0.15 s) and between MVC 0 min an MVC+VIB 8 min conditions (5:01 ± 0:17 ± 4.89 s Vs. 0.16 s). The MVC with and without the addition of mechanical vibration seems not to improve 40m sprint test after 0 and 8 min of rest.